Impact of body mass index to functional outcomes in patients after primary total hip arthroplasty - Gerard Benny Nanna; Muhammad Andry Usman; Nur Rahmansyah (Physical Therapy Journal of Indonesia, 2026)
Background: Total hip arthroplasty (THA) is a frequently performed orthopedic procedure to relieve pain and restore function in patients with degenerative or traumatic changes of the hip joint. Obesity has been identified as a potential modifier of surgical outcomes, but the literature is conflicting on the effects of obesity on postoperative functional recovery compared to non-obese populations. This study aimed to investigate the influence of preoperative body mass index (BMI) on long-term functional outcomes following primary THA, with a five-year follow-up conducted in South Sulawesi, Indonesia. Methods: A retrospective cohort study was conducted involving 30 patients who underwent primary THA at Dr. Wahidin Sudirohusodo Central General Hospital, Makassar, in 2023. Functional outcomes were assessed using the change in Harris hip score (ΔHHS), calculated from preoperative and six-month postoperative evaluations. Statistical analyses included the Shapiro-Wilk test for normality, Spearman’s rank correlation for non-parametric associations, Kruskal-Wallis and Mann-Whitney U tests for group comparisons, and multivariate linear regression to identify independent predictors of functional improvement. Results: Samples consisting of 60% female, mean age 56.8±11.0 years; 66.7% obese. Strong negative correlation between BMI and delta HHS (r=-0.949, p<0.001). Significant differences across BMI categories (p<0.001), with obese II showing the poorest outcomes. BMI was the significant primary predictor (-3.417, p<0.001), while age and gender were not. Conclusion: Higher BMI significantly correlates with poorer functional outcomes post-THA. Weight management after THA is crucial for optimizing the patient’s functional outcomes.